KONTROL SOSIAL HARIAN PALOPO POS DALAM MEWUJUDKAN GOOD GOVERNANCE DI LUWU Social Control of Palopo Pos Daily Newspaper in Realizing Good Governance at Luwu - Husain, Wahyuni (KAREBA : Jurnal Ilmu Komunikasi, 2011)
AbstractThis research is aimed to analyse the trends of good governance rubric presented at Daily Palopo Post, and role of this media in realizing good governance ini Luwu. The discussion of the research based on the question do Daily Palopo Post was able to become media control for local governance and also become mediator among the society, government party and also the private sectors. This research was performed by analyzing the trends of good governance rubric presented at Daily Palopo Post, and also the role of Palopo Post in realizing good governance during three months by using content analyse a descriptive method quantitative. The election of information technique was taken an entirely of population as sampel along MayâJune 2009. The research result shown that 1). The content of News daily Palopo Post on good governance was much more published the authority abuse based on governmental information source. That theme principle good governance also were published the accountability principle as implementation of government public responsibility; and 2) Daily Palopo Post has a role ini dissemination of information and performed social control function especially as media which stimulated public awareness in order to enabled their role in controlling governance affairs toward better good governance managementÂ AbstrakPenelitian ini bertujuan untuk menganalisis kecenderungan rubrik good governance ditampilkan di Harian Palopo Pos, dan peran Palopo Pos dalam mewujudkan good governance di Luwu. Permasalah penelitian dilatarbelakangi oleh pertanyaan apakah harian Palopo Pos mampu menjadi media kontrol bagi pemerintahan lokal serta menjadi mediator antara masyarakat, pemerintah maupun pihak swasta. Penelitian ini dilakukan dengan menganalisis tampilan rubrik good governance selama tiga bulan dengan menggunakan metode deskriptif kuantitafif analisis isi. Teknik pemilihan informasi mengambil keseluruhan populasi menjadi sampel dan dalam kurun waktu Mei-Juli 2009. Hasil penelitian menunjukkan bahwa 1). Porsi pemberitaan harian Palopo Pos yang memuat isu-isu tentang good governance lebih banyak mengangkat tema penyalahgunaan wewenang. Demikian pula tema-tema yang berkaitan dengan prinsip good governance lebih banyak memunculkan prinsip akuntabilitas sebagai perwujudan pertanggungjawaban publik dari pemerintah; dan 2) Kehadiran Harian Palopo Pos menyebabkan kontrol media ini terhadap pemerintah di Luwu makin dekat, jadi kontrol media tidak hanya ada pada level pemerintahan pusat, akan tetapi juga pada level pemerintahan di daerah.